2014
DOI: 10.3390/genes5040887
|View full text |Cite
|
Sign up to set email alerts
|

Mouse ENU Mutagenesis to Understand Immunity to Infection: Methods, Selected Examples, and Perspectives

Abstract: Infectious diseases are responsible for over 25% of deaths globally, but many more individuals are exposed to deadly pathogens. The outcome of infection results from a set of diverse factors including pathogen virulence factors, the environment, and the genetic make-up of the host. The completion of the human reference genome sequence in 2004 along with technological advances have tremendously accelerated and renovated the tools to study the genetic etiology of infectious diseases in humans and its best charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 203 publications
(263 reference statements)
0
13
0
Order By: Relevance
“…Even today, several tools are available to manipulate the mouse genome to obtain transgenic, knockout and knock‐in variants. Forward genetics is still important, as random mutagenesis can be used to gather new information on already known genes . Furthermore, a significant proportion of human diseases is caused by nucleotide variants in genes that affect their function or regulation rather than merely deactivating them .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even today, several tools are available to manipulate the mouse genome to obtain transgenic, knockout and knock‐in variants. Forward genetics is still important, as random mutagenesis can be used to gather new information on already known genes . Furthermore, a significant proportion of human diseases is caused by nucleotide variants in genes that affect their function or regulation rather than merely deactivating them .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the above, the study of animal models obtained by mutagenesis can be used to elucidate the function of genes and characterize human genetic diseases . The induction strategy for point mutations by N‐ethyl‐N‐nitrosourea (ENU) together with consistent phenotypic selection can be a powerful tool to identify mutations responsible for complex phenotypes …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkylating agents affect the mammalian genome by forming DNA lesions, and thus causing base substitution mutations, or preventing DNA replication [Imai et al, ; van Boxtel et al, ]. However, ENU has been shown to be a potent alkylating agent inducing germ cell line mutation due to its strength and preferential activity in spermatogonial stem cells [Caignard et al, ]. It has also been shown that germ cells treated with 6‐MP have the greatest response in early meiotic spermatocytes [Generoso et al, ; Norgard et al, ].…”
Section: Introductionmentioning
confidence: 99%